Development of reference ELISA assays for urinary oestrone-3 ¯-glucuronide and pregnanediol-3 ¯-glucuronide using timed urine specimens : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Binnie, Janette Elizabeth (Massey University, 1999)
Enzyme-linked immunosorbent assays (ELISA) have been developed which measure oestrone glucuronide (E1-3G) and pregnanediol glucuronide (PdG) in timed, diluted urine samples. Measurement of these urinary metabolites allows information to be collected, non-invasively, on the hormonal interplay between the ovaries and the hypothalamicpituitary axis, which determines or helps to make predictions about the potentially infertile and fertile phases of the human menstrual cycle. Immunoglobulin Class G (IgG) antibodies raised in sheep against the analyte of interest (E1-3G and PdG) were adsorbed onto polystyrene microtitre wells. The enzyme conjugate tracer was horseradish peroxidase (HRP), and was prepared by conjugation with either E1-3G or PdG using the active ester coupling procedure. A direct competitive immunoassay configuration in which both analyte and tracer were added to the wells simultaneously allowed a direct competition between them for the immobilised antibody sites. A chromogenic detection system involving o-phenylenediamine (OPD) was used for the measurement of the amount of bound tracer (HRP conjugate) which could be related to the amount of analyte in a urine sample. The sensitivity of the E1-3G assay was 3.4 nmoles/ 24 h, and for the PdG the sensitivity was 0.5 μmoles/ 24 h. Both assays were reliable, and were successfully validated against World Health Organisation (WHO) assays performed on the same urine samples in a multicentre study of the Ovarian Monitor (project #90905). The E1-3G and PdG reference assays developed in the present study are acceptable for use in the laboratory and can be used to validate new non-instrumental colour tests, or other home fertility kit assays currently being developed.
Keywords: Enzymes; Metabolites; Analysis